Кенимех районы қазақлары тилиниң изертлениўи - Қуттымуратова, Ы.А. (ILIM hám JÁMIYET, 2021)
The article provides a detailed study of the history of the Kenimex Kazakhs, as well as features in their language. The object of research is the peculiarities of the language of the Kazakhs of Kenimex district. The article reveals the invaluable heritage of Kazakh literature and rich oral tradition. It is also important that the Kazakh language is passed on to the next generation in its purest form.